Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1. Ta có: \(x^2-2xy-x+y+3=0\)
<=> \(x^2-2xy-2.x.\frac{1}{2}+2.y.\frac{1}{2}+\frac{1}{4}+y^2-y^2-\frac{1}{4}+3=0\)
<=> \(\left(x-y-\frac{1}{2}\right)^2-y^2=-\frac{11}{4}\)
<=> \(\left(x-2y-\frac{1}{2}\right)\left(x-\frac{1}{2}\right)=-\frac{11}{4}\)
<=> \(\left(2x-4y-1\right)\left(2x-1\right)=-11\)
Th1: \(\hept{\begin{cases}2x-4y-1=11\\2x-1=-1\end{cases}}\Leftrightarrow\hept{\begin{cases}x=0\\y=-3\end{cases}}\)
Th2: \(\hept{\begin{cases}2x-4y-1=-11\\2x-1=1\end{cases}}\Leftrightarrow\hept{\begin{cases}x=1\\y=3\end{cases}}\)
Th3: \(\hept{\begin{cases}2x-4y-1=1\\2x-1=-11\end{cases}}\Leftrightarrow\hept{\begin{cases}x=-5\\y=-3\end{cases}}\)
Th4: \(\hept{\begin{cases}2x-4y-1=-1\\2x-1=11\end{cases}}\Leftrightarrow\hept{\begin{cases}x=6\\y=3\end{cases}}\)
Kết luận:...
\(4x^2-2+\frac{1}{4x^2}+\left(2x\right)^2+y^2=4\)
\(\left(\left(2x\right)^2-\frac{1}{\left(2x\right)^2}\right)^2+\left(\left(2x\right)-y\right)^2=4-2\left(2x\right)y\)
\(VT\ge0\) đẳng thức khi: 2x=+-1; 2x=y;
\(\Rightarrow4-4xy\ge0\Rightarrow xy\le1\)
DS: x=+-1/2; y+-1